(untitled) (Global Journal of Human-Social Science, 2024)
At the moment there are several hypotheses in geophysics that explain especially dangerous processes of the earth s crust movements - sudden outbursts of rocks and gas from a rock mass from the point of view of classical physics Despite the fact that various macroscopic systems can be accurately described using classical mechanics and electrodynamics a real mechanism and a working model of this phenomenon cannot be built Consequently to develop a model of sudden outbursts of rocks and gas it is necessary to apply new approaches and methods different from the description of macroscopic systems This article describes a quantum version of the process of the ejection of rocks from a rock mass In particular we described the mechanism of the Coulomb explosion that occurs in the rocks of the earth s crust with a sharp change in rock pressure and built a model of the sudden release of rocks and gases In our opinion the quantum processes described by us can be sources not only of sudden outbursts and rockslide but also sources of more formidable phenomena - earthquakes and volcanic explosions